2018
DOI: 10.1111/bcpt.13185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutathione S‐transferase genetic polymorphisms on busulfan pharmacokinetics and veno‐occlusive disease in hematopoietic stem cell transplantation: A meta‐analysis

Abstract: This meta-analysis was conducted to derive an integrated conclusion about the influence of glutathione S-transferase (GST) genetic polymorphisms on busulfan pharmacokinetic (PK) parameters and veno-occlusive disease (VOD). Studies which analysed the effect of GST genetic polymorphisms on area under the curve (AUC), clearance (CL) or VOD were searched for and selected. A pooled analysis was conducted using Comprehensive Meta-Analysis programme. Nineteen studies were included in this meta-analysis. GSTA1*B and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
(51 reference statements)
1
11
1
Order By: Relevance
“…A total of 42 of patients were GSTM1 positive and 27 patients were neither GSTM1 positive or null; these patients could be carrying different alleles that are not detected by the genotyping assay. Previous studies reported that busulfan clearance is reduced among patients carrying GSTA1 *B/*B, GSTM1-null, and GSTP1 *A/*G ( 16 ).…”
Section: Resultsmentioning
confidence: 97%
“…A total of 42 of patients were GSTM1 positive and 27 patients were neither GSTM1 positive or null; these patients could be carrying different alleles that are not detected by the genotyping assay. Previous studies reported that busulfan clearance is reduced among patients carrying GSTA1 *B/*B, GSTM1-null, and GSTP1 *A/*G ( 16 ).…”
Section: Resultsmentioning
confidence: 97%
“…We identified 708 unique citations after the removal of duplicates and excluded 677 manuscripts after the title and abstract screening. After assessment of the full text, two reports on subpopulations [ 29 , 30 ] of larger studies were excluded as well as one that assessed HSCT donor genotypes [ 31 ] and one review without original data [ 23 ]. Finally, we retained 27 manuscripts ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, the heterogeneity between these studies in terms of age at HSCT, HSCT conditioning regimen, and underlying disease might have contributed to the varying results. A recent systematic review with a meta-analysis of glutathione S-transferase genes was performed by Kim et al [ 23 ]. The authors included nine studies on GSTA1*A*A versus *B haplotypes, seven studies on GSTM1 “null genotype”, and five studies on GSTP1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations